2021
DOI: 10.1159/000521467
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum Galectin-3 Levels in Patients with Sarcoidosis

Abstract: introduction: Galectin-3 is a multi-functional protein and previous studies have suggested that levels of serum galectin-3 increase in the presence of diseases that progress with pulmonary fibrosis. Therefore, the role of galectin-3 levels in the staging and assessing of the severity of sarcoidosis is investigated in the present study. Methods and Subjects: The present study was conducted on a total of 73 subjects, including 25 healthy individuals and 48 patients with a pathologically confirmed diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a cohort study conducted in Turkey, serum levels of galectin-3 were found to be significantly higher in sarcoidosis patients compared to healthy controls. Furthermore, these levels were particularly elevated in patients at stage 2 or higher of the disease [83].…”
Section: Serum Biomarkersmentioning
confidence: 94%
“…In a cohort study conducted in Turkey, serum levels of galectin-3 were found to be significantly higher in sarcoidosis patients compared to healthy controls. Furthermore, these levels were particularly elevated in patients at stage 2 or higher of the disease [83].…”
Section: Serum Biomarkersmentioning
confidence: 94%
“…Serum 3 Galectin is a β-galactoside-binding animal lectin involved in various processes such as cell growth, angiogenesis and inflammation. Mean galectin levels are significantly higher in patients with pulmonary parenchymal involvement; thus, it is particularly associated with patients in stage II, III or IV of the Scadding classification [24 ▪▪ ].…”
Section: Summary Of Biomarkers Research In Sarcoidosismentioning
confidence: 96%
“…B4GALT1, an enzyme that synthesizes LacNAC, is found to be overexpressed in patients with IPF ( 86 ). Moreover, level of galectin 3 (GAL3), is increased in patients of pulmonary sarcoidosis ( 87 ) and fibrosis ( 88 ) and targeting GAL3 by small molecule inhibitors was showed efficacious in mouse models of bleomycin-induced lung fibrosis ( 89 ). Recent studies have linked LacNAc and LacdiNAc dissacharides with the process of granuloma formation, suggesting a pro-inflammatory role for these molecules ( 84 ) in IPF and sarcoidosis.…”
Section: Structure and Synthesis Of Glycansmentioning
confidence: 99%